The Scientific Movement of State Islamic University of Imam Bonjol Padang - Wirman, Eka Putra (Madania: Jurnal Kajian Keislaman, 2019)
This article aims to describe the paradigm and scientific philosophy of State Islamic University of Imam Bonjol Padang that has just been transformed from State Institute for Islamic Studies (IAIN) into State Islamic University (UIN). Hence, a qualitative method is used to gather data by using documentation and interview. In addition, a focus group discussion was employed to get valid information. The result of the study indicates that the  State Islamic University of Imam Bonjol adopts an interaction-dialogue paradigm. This offers every discipline to collaborate and produce integrated sciences by positioning Islam, cultures, and science as the sources of knowledge equally. Then, these three sources act together as the basis of knowledge to create benefits for humanity.